2020
DOI: 10.1080/10413200.2020.1716871
|View full text |Cite
|
Sign up to set email alerts
|

Elite female soccer players’ dual career plans and the demands they encounter

Abstract: An increasing number of female soccer players are playing at the elite level. It is important to encourage these players to remain mindful of the benefits of carrying out a dual career (e.g., higher education and elite sport path). The current study provides an investigation of players' dual career plans and the demands they encounter. The guiding framework used within the research was the Push-Pull theoretical framework. Semi-structured interviews were conducted with eleven participants, encapsulating a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 29 publications
6
31
0
2
Order By: Relevance
“…Although this study limited to one sport, football, it made a point that the junior athletes in their study tended to believe that DC pathways made success in either area harder to achieve. In line with this, Harrison, et al (2020) found out that DC difficulties were increased when the junior athletes' level of education increased (i.e., from school to university and from university to vocation). In the case of Slovakia, it was found that junior athletes might develop a negative attitude towards their DC by their educational institutions (Geraniosova &Ronkainen, 2015).…”
Section: Barriers and Challenges For Junior Athletes With DCmentioning
confidence: 55%
“…Although this study limited to one sport, football, it made a point that the junior athletes in their study tended to believe that DC pathways made success in either area harder to achieve. In line with this, Harrison, et al (2020) found out that DC difficulties were increased when the junior athletes' level of education increased (i.e., from school to university and from university to vocation). In the case of Slovakia, it was found that junior athletes might develop a negative attitude towards their DC by their educational institutions (Geraniosova &Ronkainen, 2015).…”
Section: Barriers and Challenges For Junior Athletes With DCmentioning
confidence: 55%
“…There was substantial variation in the SAMSAQ-PT dimension scores by sex, university type, and sport level. The observed substantial gender-related variation in SM and CM could be due to lower dual career support for Brazilian female athletes and limited economic opportunities for top-level women's sport (Harrison et al, 2020). Coherently, during the academic path, the highest effect scores for AM emerged for female student-athletes, who might emphasize more their academic career concerning their sports career (Tekavc, Wylleman & Cecić-Erpič, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It appears that young sporting women are often more committed to combining sporting and educational goals and identities than are sporting men. Despite the growing professionalisation of women’s football (soccer) in Britain, many young players also invest in academic excellence (Harrison et al, 2020). In this latter study, one female participant explained: ‘I wanted to do really well in uni, I didn’t want to go there and just pass, you know I still want a first.…”
mentioning
confidence: 99%
“…In this latter study, one female participant explained: ‘I wanted to do really well in uni, I didn’t want to go there and just pass, you know I still want a first. And then again with soccer, I want to do the best that I can’ (Harrison et al, 2020: 16). Despite the growth of women’s sport, however, there remains a staggering structural inequality of opportunity that limits women’s social agency in developing a professional athletic career.…”
mentioning
confidence: 99%